Ultrathin lead alloy substrate of lead-acid storage battery as well as preparation process and application of ultrathin lead alloy substrate

By employing techniques such as segmented rolling, hydraulic control, and warm rolling with air cooling, the problem of excessively thick lead-acid battery substrates has been solved, enabling the stable preparation of ultra-thin substrates and improving battery performance. This has reduced production costs and increased the flexibility of battery structure design.

CN120961627APending Publication Date: 2025-11-18JIESHOU HUAYU POWER SUPPLY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202511322481.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

The existing lead-acid battery substrates are relatively thick, resulting in high lead consumption, inflexible battery structure design, and the ultra-thin substrates are prone to wrinkles, breakage, and large thickness deviations during the rolling process, making it difficult to meet the needs of industrial production.

Method used

By employing a segmented rolling strategy, a hydraulic automatic thickness control system, hard chrome-plated rolls, and water-based lubricant, combined with warm rolling and air cooling devices, the fine processing control of lead strip is achieved, reducing the temperature of the lead strip and ensuring smooth winding.

Benefits of technology

Stable preparation of ultra-thin lead alloy substrates has been achieved, reducing lead consumption, improving the flexibility and performance of battery structure design, solving problems such as uneven thickness, edge defects and lead sticking to rollers, and improving production efficiency and battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120961627A_ABST
    Figure CN120961627A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrathin lead alloy substrate of a lead-acid storage battery as well as a preparation process and application of the ultrathin lead alloy substrate, and belongs to the technical field of preparation of lead-acid storage batteries. The technology adopts a nine-pass segmented rolling strategy: a rough rolling stage (1-3 passes, the reduction rate is 15-20%) eliminates casting structure defects, an intermediate rolling stage (4-6 passes, 10-15%) stabilizes material flow, and a finish rolling stage (7-9 passes, 5-8%) controls thickness precision; and meanwhile, a roller hard chromium coating, hydraulic AGC dynamic adjustment, 100-150 DEG C warm rolling, a water-based lubricant, finish rolling air cooling and a power winding device are combined, and 10 or more passes can be adapted to prepare thinner substrates. The thickness of the substrate prepared through the technology is 0.25-0.3 mm, the tolerance is smaller than or equal to + / -0.009 mm, the tensile strength is larger than or equal to 17.5 MPa, and the rolling wrinkle rate is smaller than or equal to 0.5%; when the material is applied to a grid, the 5C capacity retention ratio of a battery is greater than or equal to 88.3%, and the material has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of lead-acid battery preparation, and particularly relates to an ultrathin lead alloy substrate for lead-acid batteries and a preparation process and application thereof. BACKGROUND

[0002] With the continuous improvement of the cost performance requirements of new energy industries for energy storage equipment and the direct impact of raw material price fluctuations on the production cost of lead-acid batteries, the industry urgently needs to achieve a synergistic breakthrough of "cost reduction and efficiency improvement" and "performance upgrade" through process optimization. Among them, the continuous casting and rolling punching process has gradually replaced the traditional gravity casting and pressure casting process and become the mainstream technology route for the preparation of lead-acid battery grids due to its high production efficiency, uniform substrate organization and good grid forming precision.

[0003] In the cost composition of lead-acid batteries, the proportion of lead material cost is as high as 60%-70%, and the thickness of the lead strip substrate, as the core substrate of the grid, directly determines the lead material consumption per battery. Under the existing continuous casting and rolling punching process system, the thickness of the lead strip substrate is generally maintained at ≥0.6mm due to the precision of the rolling equipment, the plasticity of the lead alloy material and the process control level. For example, the battery plate continuous rolling process for automobiles disclosed in patent CN103181019B reduces the lead casting blank with an initial thickness of 8-11mm to 0.8-1.2mm through 7-10 passes, which achieves a certain degree of thinning, but the final thickness is still higher than 0.6mm, and the rolling stability of the ultrathin strip material is not optimized; the continuous casting and rolling process for valve-regulated lead-acid batteries proposed in patent CN106025383A controls the thickness of the lead strip substrate to be 0.6-2.5mm, and the core improvement point is the polygonal shaping design of the grid rib, rather than the breakthrough thinning of the substrate thickness; although the powder rolling process in patent CN102005574A reduces the substrate thickness to 0.2mm, this technology relies on the mixing and pressing of lead powder and additives, and the production process is complex and the cost is high. Moreover, the powder metallurgy bonding strength is difficult to meet the mechanical requirements of high-power discharge scenarios, and cannot replace the mainstream continuous casting and rolling process.

[0004] There are two major limitations in the existing technology: on the one hand, the substrate with a thickness of ≥0.6mm leads to a high lead material consumption, which restricts the further reduction of battery cost; on the other hand, the thick substrate limits the flexibility of battery structure design: for example, in scenarios such as automotive start-stop batteries and high-rate energy storage batteries that have clear requirements for large-current discharge performance, if the negative plate substrate thickness can be further thinned, more plates can be designed in the same battery shell, but the existing process cannot achieve the fine processing scheme of stable preparation of ultrathin substrates, leading to problems such as wrinkles, fractures and large thickness deviations of ultrathin strips during rolling, which are difficult to meet the requirements of industrial production. SUMMARY

[0005] One of the purposes of the present application is to provide a preparation process of a lead acid battery ultra-thin lead alloy substrate, further thinning the lead acid battery lead strip substrate thickness, while providing more optimization possibilities for battery design (such as improving the specific scene high-current discharge requirement by matching multiple plates), and realizing more fine processing control of the ultra-thin lead strip.

[0006] The second purpose of the present application is to provide a lead acid battery ultra-thin lead alloy substrate prepared by the above preparation process of a lead acid battery ultra-thin lead alloy substrate.

[0007] The third purpose of the present application is to provide an application of a lead acid battery ultra-thin lead alloy substrate in a lead acid battery grid, and the application of the lead acid battery ultra-thin lead alloy substrate is the above-mentioned lead acid battery ultra-thin lead alloy substrate.

[0008] The purpose of the present application can be achieved by the following technical solutions: A preparation process of a lead acid battery ultra-thin lead alloy substrate adopts a segmented rolling strategy, including the following steps: S1, rough rolling stage: 1-3 passes, reduction rate is 15%-20%; S2, medium rolling stage: 4-6 passes, reduction rate is 10%-15%; S3, finishing rolling stage: 7-9 passes, reduction rate is 5%-8%; The surface of the roller is treated with hard chromium plating during the segmented rolling process, and the roll gap is dynamically adjusted by combining a hydraulic automatic thickness control system; The rolling process adopts a water-based lubricant and adds a forced air cooling device in the finishing rolling stage to reduce the lead strip temperature; A power conveying device is added in the winding stage after the finishing rolling stage, the winding tension and speed are controlled by active power, the winding process is smooth, and the lead alloy substrate is obtained.

[0009] Further, the rolling temperature is controlled at 100-150℃, the rolling speed of the first 3 passes is 10-15m / min, the fourth to sixth passes is 15-20m / min, and the seventh to ninth passes is 20-30m / min.

[0010] Further, the roller is one of a flat roller or a micro-crown roller.

[0011] Further, the plating thickness of the hard chromium plating layer on the surface of the roller is 5-10μm.

[0012] Further, the Vickers hardness of the hard chromium plating layer on the surface of the roller is ≥800HV.

[0013] Further, the hydraulic automatic thickness control system is used to ensure that the lead belt is uniformly extended along the width direction.

[0014] Further, the water-based lubricant is prepared by mixing Jasper-RLF901 emulsified cutting fluid and water at a volume ratio of 1: (180-220).

[0015] Further, the lead belt temperature is reduced to ≤40℃.

[0016] Further, the active power control winding tension is stabilized at 50N±2N.

[0017] Further, the rolling pass can also be ≥10, and when the rolling pass is ≥10, the segmented rolling strategy is adjusted as follows: the rough rolling stage is the 1st-4th pass, the reduction is 12%-18%; the medium rolling stage is the 5th-8th pass, the reduction is 8%-13%; the finish rolling stage is the 9th pass and subsequent passes, the reduction is 4%-7%, and the rolling temperature, rolling speed, roll control and winding control of each stage are adapted to the process parameters of the corresponding stage when the 9th pass is rolled.

[0018] A lead-acid battery ultra-thin lead alloy substrate is prepared by the preparation process of the above-mentioned lead-acid battery ultra-thin lead alloy substrate.

[0019] The application of a lead-acid battery ultra-thin lead alloy substrate in a lead-acid battery grid, the lead-acid battery ultra-thin lead alloy substrate applied is the above-mentioned lead-acid battery ultra-thin lead alloy substrate.

[0020] The beneficial effects of the present application are: (1) The present application adopts a 9-pass segmented rolling strategy (rough rolling 15%-20%, medium rolling 10%-15%, finish rolling 5%-8%), reduces the thickness of the lead belt substrate, reduces the lead material usage under the same area, and realizes the industrialized production of ultra-thin substrates in the continuous casting and rolling process. When applied to the lead-acid battery grid, the battery structure is more compact, the ultra-thin substrate can reduce the thickness of the pole plate under the same capacity, making the overall volume of the battery smaller and the weight lighter; conversely, the number of pole plates can be increased under the same volume, improving the battery capacity. The segmented rolling refines the lead belt grain structure, making the tensile strength and ductility of the substrate more optimal, prolonging the service life of the battery.

[0021] (2) The present application adopts a hydraulic automatic thickness control system (hydraulic AGC) dynamic roll gap adjustment and hard chromium plating roll design, combined with the reduction rate control in the finish rolling stage, to reduce the lead belt thickness tolerance and improve the surface finish, solving the problems of uneven thickness, edge defects and lead sticking to the roll that often occur in the existing ultra-thin strip rolling. At the same time, the 100-150℃ warm rolling interval and the multi-pass deformation heat sharing mechanism avoid the grain coarsening caused by local overheating of the lead material, ensuring the improvement of substrate organization density and mechanical properties.

[0022] (3) The application adopts a water-based lubricant combined with a finish rolling air cooling device to reduce the residual amount of the lubricant on the surface of the lead strip, control the finish rolling temperature, and reduce the cost of subsequent cleaning processes; the newly added power conveying and winding device solves the problems of wrinkles and deformation in the existing non-powered winding and re-production, realizes continuous and stable winding, and improves the production efficiency. BRIEF DESCRIPTION OF DRAWINGS

[0023] The application will be further described below with reference to the drawings.

[0024] Figure 1 is a schematic diagram of the preparation process of Example 1 of the application; Figure 2 is a schematic diagram of the preparation process of Comparative Example 1 of the application. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned purposes, features and advantages of the application more obvious and easy to understand, the specific embodiments of the application will be described in detail below.

[0026] The application provides a preparation process of an ultrathin lead alloy substrate of a lead-acid storage battery, comprising the following steps: 1. Pass distribution and reduction rate optimization Segmented rolling strategy: coarse rolling stage (first 3 passes): thinning quickly with a large reduction rate (15%~20%) to eliminate casting organizational defects.

[0027] Medium rolling stage (4th~6th passes): medium reduction rate (10%~15%), gradually adjusting the thickness and stabilizing the material flow.

[0028] Finish rolling stage (7th~9th passes): small reduction rate (5%~8%), focusing on controlling the thickness tolerance and surface quality.

[0029] Cumulative deformation distribution: the total reduction amount remains unchanged, but is distributed to more passes, and the original 7-pass total reduction rate of 80% is changed to a 9-pass gradual realization.

[0030] 2. Roll pass and roll gap design

[0031] Pass optimization: flat or slightly convex rollers are used, flat rollers are suitable for narrow lead strips and can ensure the flatness of the strip; slightly convex rollers are suitable for wide lead strips and can compensate for the "edge thinning" phenomenon during rolling, so that the full width thickness difference is ≤0.005mm, which meets the preparation needs of different specifications of battery grid; combined with dynamic roll gap adjustment technology (hydraulic AGC), the uniformity of lead strip extension in each pass is ensured.

[0032] Roll surface treatment: increase the roll surface plating (hard chrome), reduce the lead sticking phenomenon, prolong the roll life. When the plating thickness is <5 μm, the wear resistance is insufficient, and the lead material is easy to scratch, resulting in surface defects of the strip; when the thickness is >10 μm, the plating and the roll base bonding force decreases, and it is easy to fall off and contaminate the lead strip. Limiting the roll base Vickers hardness can improve the surface wear resistance, effectively block the diffusion of lead atoms to the roll surface, reduce the scratches caused by "lead sticking" from the root, and reduce the roll grinding frequency, saving maintenance costs.

[0033] 3. Temperature control and process parameters

[0034] Warm rolling process: the melting point of lead is low (327℃), and the rolling temperature needs to be controlled in the range of 100~150℃. When the temperature is lower than 100℃, the plasticity is insufficient, which easily leads to rolling cracking; when the temperature is higher than 150℃, local overheating is easily caused by concentrated deformation heat, which avoids local overheating leading to grain coarsening through multiple passes to share the deformation heat.

[0035] Rolling speed matching: coarse rolling 10~15 m / min can ensure that the casting structure is fully broken (eliminate defects such as porosity and segregation), medium rolling 15~20 m / min realizes smooth transition, and finishing rolling 20~30 m / min improves production efficiency on the premise of ensuring thickness accuracy, which has a great improvement in process efficiency compared with the existing single speed (15~20 m / min) process.

[0036] 4. Lubrication and cooling system

[0037] Lubricant selection: water-based lubricant (Jasper-RLF901 emulsified cutting fluid, mixed with water at a ratio of 1:(180-220)) is used to reduce the residue on the surface of the lead strip. When the concentration is too high, the residue of the lubricant is too high, and additional cleaning process is needed; when the concentration is too low (such as 1:300), the lubrication effect is insufficient, which easily leads to surface wrinkling of the strip. 1:180-220 does not need additional cleaning, and the anti-rust component of Jasper-RLF901 can make the lead strip not oxidize and rust within 72 hours.

[0038] Segmented cooling: add a wind cooling device in the finishing rolling stage to control the finishing rolling temperature ≤40℃. If the finishing rolling temperature is >40℃, the lead strip is easy to deform due to residual heat when winding, and a flattening process is needed later; through the wind cooling device, the temperature is reduced to ≤40℃, and the flatness of the lead strip after winding is ≤1 mm / m, which saves the flattening step and avoids surface oxidation caused by high temperature, improving the conductivity of the substrate.

[0039] 5. Optimization design of winding The existing design winding stage has no power transmission device, and relies on the driving of the rear rotating wheel for winding. When the thickness of the lead tape is below 0.4 mm, the lead tape is severely deformed and cannot meet the normal production. The new design increases the power transmission device, and the tension is stabilized at 50 N±2 N, so that the winding is smooth and meets the needs of normal production.

[0040] In some embodiments, the rolling pass can also be ≥10 passes. When the rolling pass is ≥10 passes, the segmented rolling strategy is adjusted as follows: the rough rolling stage is the first to fourth pass, the reduction rate is 12% to 18%; the medium rolling stage is the fifth to eighth pass, the reduction rate is 8% to 13%; the finish rolling stage is the ninth pass and subsequent passes, the reduction rate is 4% to 7%, and the rolling temperature, rolling speed, roll control and winding control of each stage are adapted to the process parameters of the corresponding stage when rolling 9 passes.

[0041] When thinner substrates are prepared, by increasing the rough rolling pass and reducing the single pass reduction rate (from 15% to 20% to 12% to 18%), the deformation amount of each pass can be evenly distributed, the cumulative deformation heat is easier to control, and the risk of cracking is avoided. At the same time, the finish rolling reduction rate is reduced to 4% to 7%, which can further improve the thickness accuracy and expand the adaptability of the process to different thickness substrates.

[0042] The specific embodiments of the present application are described in detail below, but it should be understood that the protection scope of the present application is not limited by the specific embodiments.

[0043] Example 1

[0044] The present embodiment provides a lead-acid battery ultra-thin lead alloy substrate, which is prepared by the following steps: I. Raw material pretreatment Continuous casting blank forming: using a horizontal continuous casting machine to cast molten lead alloy (temperature 350℃) into a blank with a thickness of 5.0 mm, a width of 200 mm and a length of 50 m, and the cooling speed of the blank is controlled at 15℃ / s to avoid coarse grains; Blank surface treatment: polish the surface oxide layer of the blank with 120 mesh sandpaper until the metal luster is exposed, then clean it with anhydrous ethanol, and the surface roughness Ra after drying is ≤2.0μm.

[0045] II. Pre-rolling equipment

[0046] Coating treatment: using electroplated hard chromium process, coating thickness 8μm, Vickers hardness 850HV; Lubricant preparation: Jasper-RLF901 emulsified cutting fluid mixed with deionized water at a volume ratio of 1:200; III. Specific operation of 9-pass segmented rolling (I) Rough rolling stage (first to third pass, eliminate casting defects) Pass 1 : the pretreated slab is sent into the rolling mill, the inlet temperature is 25℃, the reduction is 18%, the roll gap is 4.1mm, the roll temperature is 120℃, and the speed is 12m / min; Pass 2: the reduction is 17%, the roll gap is 3.47mm, the roll temperature is 125℃, and the speed is 12m / min; Pass 3: the reduction is 16%, the roll gap is 2.91mm, the roll temperature is 130℃, and the speed is 12m / min; (II) the intermediate rolling stage (Passes 4~6, stabilizing thickness and flow) Pass 4: the reduction is 13%, the roll gap is 2.52mm, the roll temperature is 130℃, the speed is 16m / min, and the lubricant spraying is started; Pass 5: the reduction is 12%, the roll gap is 2.20mm, the roll temperature is 128℃, and the speed is 16m / min; Pass 6: the reduction is 11%, the roll gap is 1.94mm, the roll temperature is 125℃, and the speed is 16m / min; (III) the finishing rolling stage (Passes 7~9, controlling precision and surface) Pass 7: the reduction is 7%, the roll gap is 1.79mm, the roll temperature is 120℃, the speed is 25m / min, and the air cooling is started; Pass 8: the reduction is 6%, the roll gap is 1.67mm, the roll temperature is 118℃, and the speed is 25m / min; Pass 9: the reduction is 5%, the roll gap is 1.58mm, the roll temperature is 115℃, and the speed is 25m / min; IV. Winding Winding operation: the lead strip enters the power winding device, the tension is stabilized at 50N±2N, the winding diameter increases from Φ100mm to Φ500mm, and the lead strip is not wrinkled or deviated after winding.

[0047] The above steps are shown in Figure 1 .

[0048] V. Application

[0049] The lead strip is punched into a grid (grid rib 1.2mm×1.0mm, aperture 6mm×8mm), coated with lead paste, and assembled into a 12V / 60Ah lead-acid storage battery.

[0050] Example 2

[0051] Compared with Example 1, the difference lies in the pass distribution: rough rolling 1~3 passes (20%, 19%, 18%), intermediate rolling 4~6 passes (15%, 14%, 13%), and finishing rolling 7~9 passes (8%, 7%, 6%); The remaining raw materials and preparation process remain the same as those of Example 1.

[0052] Example 3

[0053] The difference between this example and Example 1 is that the roll is a micro-crowned roll (crown 0.02 mm); The rest of the raw materials and the preparation process remain the same as Example 1.

[0054] Example 4

[0055] The difference between this example and Example 1 is that the volume ratio of Jasper-RLF901 and water is 1:180; The rest of the raw materials and the preparation process remain the same as Example 1.

[0056] Example 5

[0057] The difference between this example and Example 1 is that the pass distribution is: rough rolling 1~4 passes (15%, 14%, 13%, 12%), medium rolling 5~8 passes (10%, 9%, 8%, 7%), and finish rolling 9~10 passes (6%, 5%); the target thickness of the lead alloy substrate is 0.25 mm; The rest of the raw materials and the preparation process remain the same as Example 1.

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that a traditional rolling process of 7 passes is used, and the steps are as shown in Figure 2 ; Pass distribution: 7 passes (reduction rate 25%, 20%, 15%, 10%, 8%, 6%, 5%); Roll: uncoated flat roll; Temperature: 150~180℃ (without precise control); Winding: no power winding; Others: no AGC, lubricant is machine oil (1:50); The rest of the raw materials and the preparation process remain the same as Example 1.

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 1 is that the roll used has no hard chromium plating (base hardness 250 HV); The rest of the raw materials and the preparation process remain the same as Example 1.

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 1 is that the roll gap in the 9-pass AGC-free system process is manually adjusted; The rest of the raw materials and the preparation process remain the same as Example 1.

[0064] Comparative Example 4

[0065] The difference between the present comparative example and Example 1 is that the temperature adjustment in the 9-pass high-temperature rolling process is 160-180°C. The remaining raw materials and preparation process remain the same as in Example 1.

[0066] Performance test

[0067] 1. Substrate thickness and tolerance: A laser thickness gauge (accuracy ±0.001 mm) was used to measure 3 points every 100 mm along the length of the strip, and the average value and maximum deviation were taken; 2. Surface finish: A roughness meter was used to measure the Ra value (μm); 3. Tensile strength: According to GB / T228.1-2021 "Metallic Materials Tensile Test Part 1: Room Temperature Test Method", a universal testing machine was used for testing; 4. Winding wrinkle rate: The proportion of the length of the surface wrinkle of the strip after winding to the total length was counted; 5. Battery high-current discharge performance: After the substrate was made into a grid, a 12V / 60Ah lead-acid battery was assembled, and the capacity retention rate at 5C rate (relative to 2C rate) was tested.

[0068] The results are shown in Table 1: Table 1

[0069] As can be seen from Table 1, the thickness of the substrates of Examples 1-5 is controlled at 0.25-0.3 mm, which is significantly thinner than 0.72 mm of Comparative Example 1, among which Example 5 further reduces the thickness to 0.25 mm through 10-pass optimization, proving that the process can adapt to the preparation needs of thinner substrates and expand application scenarios.

[0070] The winding wrinkle rate of Examples 1-5 is only 0.2%-0.5%, which is much lower than 12.5% of Comparative Example 1, indicating that the newly added power conveying device effectively solves the problem of deformation of ultra-thin strip winding, meeting the requirements of continuous production. Thickness reduction reduces the amount of lead material used under the same area, significantly reducing the cost of battery raw materials; at the same time, 0.25-0.3 mm ultra-thin substrates can achieve smaller battery volume or more plates under the same volume (such as 0.25 mm substrate of Example 5 compared to 0.3 mm substrate of Example 1, 10% more plates can be loaded in the same shell), which confirms the advantages of more compact battery structure and improved capacity.

[0071] The surface Ra and winding wrinkle rate of Example 1 are significantly reduced compared to Comparative Example 2, indicating that the high hardness of the hard chromium plating layer effectively reduces surface scratches caused by lead sticking to the roller, solving the technical problem of "lead sticking to the roller" and improving the surface finish.

[0072] The thickness tolerance of Example 1 is greatly improved compared to Comparative Example 3, and the tolerance of Example 3 is further reduced, indicating that the dynamic adjustment capability of the hydraulic AGC solves the problems of uneven extension in the width direction and thickness fluctuation, and ensures the size consistency of the ultra-thin strip.

[0073] The tensile strength of Example 1 is significantly improved compared to Comparative Example 4, because the temperature rolling interval of 100-150°C in the present application divides the deformation heat by multiple passes, avoiding the grain coarsening caused by high temperature in Comparative Example 4. The tensile strength of Example 3 (micro-crown roller) reaches 19.5 MPa, further proving that the synergy of roller design and warm rolling can optimize the microstructure density and solve the problem of insufficient mechanical properties.

[0074] The 5C capacity retention rate of Example 1 is 88.5%, while that of Comparative Example 1 is only 65.2%, and that of Example 5 is further increased to 91.3%, because the ultra-thin substrate allows more number of polar plates to be placed in the same shell, expanding the reaction area and shortening the ion diffusion path, thereby improving the battery performance.

[0075] The above disclosure is only a few specific embodiments of the present application, but the embodiments of the present application are not limited thereto, and any changes that can be thought of by those skilled in the art shall fall within the protection scope of the present application.

Claims

1. A process for preparing an ultrathin lead alloy substrate for lead-acid batteries, characterized in that, The segmented rolling strategy includes the following steps: S1, Rough rolling stage: Passes 1-3, reduction rate 15%-20%; S2, intermediate rolling stage: passes 4 to 6, reduction rate 10% to 15%; S3, Finishing rolling stage: Passes 7-9, reduction rate 5%-8%; During the segmented rolling process, the surface of the rolls is treated with hard chrome plating, and the roll gap is dynamically adjusted in combination with a hydraulic automatic thickness control system. The rolling process uses a water-based lubricant and adds an air-cooling device in the finishing rolling stage to reduce the temperature of the lead strip; After the finishing rolling stage, a power conveying device is added to the winding stage. The winding tension and speed are controlled by active power to make the winding process smooth and obtain the lead alloy substrate.

2. The preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to claim 1, characterized in that, The rolling temperature is controlled at 100~150℃, the rolling speed for the first to third passes is 10~15m / min, the rolling speed for the fourth to sixth passes is 15~20m / min, and the rolling speed for the seventh to ninth passes is 20~30m / min.

3. The preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to claim 1, characterized in that, The roll is either a flat roll or a slightly convex roll.

4. The preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to claim 1, characterized in that, The thickness of the hard chrome plating on the surface of the roll is 5~10μm; the Vickers hardness of the hard chrome plating on the surface of the roll is ≥800HV.

5. The preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to claim 1, characterized in that, The hydraulic automatic thickness control system is used to ensure that the lead strip extends uniformly along the width direction.

6. The preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to claim 1, characterized in that, The water-based lubricant is prepared by mixing Jasper-RLF901 emulsified cutting fluid and water at a volume ratio of 1:(180-220); the temperature of the lead strip is reduced to ≤40℃.

7. The preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to claim 1, characterized in that, The active power control stabilizes the winding tension at 50N±2N.

8. The preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to claim 1, characterized in that, When the number of rolling passes is ≥10, the segmented rolling strategy is adjusted as follows: the roughing stage consists of passes 1 to 4 with a reduction rate of 12% to 18%; the intermediate rolling stage consists of passes 5 to 8 with a reduction rate of 8% to 13%; and the finishing rolling stage consists of pass 9 and subsequent passes with a reduction rate of 4% to 7%. The rolling temperature, rolling speed, roll control, and coiling control of each stage are adapted to the process parameters of the corresponding stage when rolling 9 passes in claim 1.

9. An ultra-thin lead alloy substrate for lead-acid batteries, characterized in that, It is prepared by the preparation process of the ultra-thin lead alloy substrate for lead-acid batteries according to any one of claims 1-8.

10. The application of an ultra-thin lead alloy substrate for lead-acid batteries in lead-acid battery grids, characterized in that, The ultra-thin lead alloy substrate for lead-acid batteries used is the ultra-thin lead alloy substrate for lead-acid batteries as described in claim 9.

Citation Information

Patent Citations

  • Light plate grid for lead-acid storage battery and preparation method thereof

    CN102005574A

  • Automobile battery and electrode plate manufacturing method

    CN103181019B

  • Valve-control type lead acid storage battery and preparation method thereof

    CN106025383A

  • Continuous-rolling production line of continuous-casting and continuous-rolling lead belt for preparing slab lattice

    CN102407235A

  • Production process of grid of lead-acid storage battery for electric moped

    CN103400994A